Seen and unseen : technology, social media, and the fight for racial justice - Hill, Marc Lamont; Brewster, Todd (Atria Books, an imprint of Simon & Schuster, Inc., 2022)
"A riveting exploration of how the power of visual media over the last few years has shifted the narrative on race and reignited the push towards justice by the New York Times bestselling author of the "worthy and necessary" (The New York Times) Nobody, Marc Lamont Hill, and the bestselling author and acclaimed journalist Todd Brewster. With his signature "clear and courageous" (Cornel West) voice Marc Lamont Hill and New York Times bestselling author Todd Brewster weave some of the most pivotal recent moments in the country's racial divide--the killings of George Floyd and Ahmaud Arbery and the harassment of Christian Cooper--into their historical context. In doing so, they reveal the common thread between these harrowing incidents: video recordings and the immediacy of technology has irrevocably changed our conversations about race and in many instances tipped the levers of power in favor of the historically disadvantaged. Drawing on the powerful role of technology as a driver of history, identity, and racial consciousness, Seen and Unseen asks why, after so much video confirmation of police violence on people of color, it took the footage of George Floyd to trigger an overwhelming response of sympathy and outrage? In the vein of The New Jim Crow and Caste, Seen and Unseen incisively explores what connects our moment to the history of race in America but also what makes today different from the civil rights movements of the past and what it will ultimately take to push social justice forward"--